Effective Antihypertensive Strategies for High-Risk Patients With Diabetic Nephropathy. (1st December 2010) - Van Buren, Peter Noel; Adams-Huet, Beverley; Toto, Robert Daniel
Abstract : Aim: Clinical guidelines recommend blood pressure (BP) lowering and renin-angiotensin-aldosterone system inhibition to slow kidney disease progression in patients with diabetic nephropathy. This study's purpose was to determine whether an antihypertensive regimen including a maximally dosed angiotensin-converting enzyme inhibitor could safely achieve target BP in indigent, predominantly minority patients with this disease. Methods: We studied 81 hypertensive adults (52% Hispanic and 31% African American) with nephropathy attributed to type 1 or 2 diabetes during the run-in period of a randomized controlled trial. The subjects received lisinopril titrated to 80 mg daily and additional antihypertensives to target a systolic BP (SBP) lower than 130 mm Hg. Blood pressure and serum potassium level were measured weekly, and a 4-gram sodium diet was prescribed. The primary outcome variable was SBP change from screening to randomization. Success in achieving SBP goal, change in urine albumin-creatinine ratio, hyperkalemia (serum potassium ≥5.5 mmol/L) and hypotension (SBP < 100 mm Hg) were also analyzed. Results: The median SBP decreased from 144 to 133 mm Hg (median change, −9.6%.) Fifty-eight (71%) achieved goal SBP during run-in. The median UACR decreased from 206.8 to 112.7 mg/mmol (median change, −42.7%). The UACR reduction correlated with SBP reduction. Seventeen subjects experienced hyperkalemia responsive to dietary/medical management. Two subjects experienced hypotension responsive to medication adjustments. Conclusion: A regimen using a maximally dosed angiotensin-converting enzyme inhibitor is safe and effective for achieving BP goal in high-risk, predominantly minority patients with diabetic nephropathy. Implementing this regimen necessitates close monitoring of serum potassium level.